Pemahaman guru matematik Tahun Enam tentang pembahagian nombor bulat / Hoi Sim Min - Hoi , Sim Min (2018)
This study is based on the theory of radical constructivism which aims to identify Year Six Mathematics teachers' understanding of the division of whole numbers. The design of this study is a case study involving six primary school mathematics teachers in Selangor and Melaka who were selected through specific purposive sampling method. Data was collected through five clinical interviews involving mental images, representations, meaning, reasoning and problem solving, which was captured on video. The results showed that the mental images of division of whole numbers of teachers are classified into five categories, namely symbolic, conceptual, procedural, figurative, and practical. In addition, representation number sentences of division of teachers are classified into four categories, namely figurative, operative, procedural and symbolic, while the representation diagrams of continuous and discrete of division of whole numbers can only be classified in one category, that is symbolic. The study also found that teachers have four interpretations of the meaning of division, four interpretations of the meaning of divisor, six interpretations of the meaning of quotient, and five interpretations of the meaning of dividend respectively. In addition, teachers have two reasonings in problem solving involving division of whole numbers, namely deductive reasoning and inductive reasoning. This study also found that teachers have four general patterns of thought and an algorithm to solve the problem of division of whole numbers, that is, the general pattern of thought of partition, measurement, repeated subtraction, the inverse of multiplication , and long division algorithm. In conclusion, teachers construct a general pattern of thought of division of whole numbers in the context of doing arithmetic activities and they form the interconnections between different general patterns of thought that are used to give meaning to a particular situation. The implications of this study include further research to identify whether the general pattern of thought of the division of whole numbers of teachers is developed in certain stages. Even though continuous and discrete materials are important in helping teachers generate meaning of division of whole numbers, efforts must be made to help teachers make the reflection and abstraction of their activities.